A study on why the Skim Amanah Saham Nasional is not fully subscribed by investors / Azlan Mohd Alias - Mohd Alias, Azlan (2006)
Skim Amanah Saham Nasional (SASN) was first introduced in 20 April, 1981 which is the first unit trust been introduced by ASNB. The introduced of SASN is one of the ways to achieve the objective of at least 30% ownership of the corporate sector by Bumiputera investors by the year 1990. This is due to the government policy in the New Economy Policy (NEP) which is introduced in 1970.